The high level of parents' attention in vocational school student career planning - Atikah Rahmah Nasution; A. Muri Yusuf; Febri Wandha Putra (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2021)
This study aims to determine the attention of parents in student career planning. This type of research is quantitative with a descriptive approach. The population in this study were students of class X SMK, amounting to 231 people. The research sample was taken using purposive sampling technique by using the criteria of students who live with their parents. So that the sample size is 171 students. The instrument in this study was a Likert scale model with five alternative answers and a questionnaire containing statements about parental attention in student career planning. Data were analyzed using the Rasch Model application and using descriptive statistics. The results of the study show that the parental attention instrument is very good for measuring the parental attention that students have. In addition, the results also show that there are students who have parental attention who are in the medium, high, very high, and low categories.